2021
DOI: 10.3389/fmicb.2021.725074
|View full text |Cite
|
Sign up to set email alerts
|

Harness Organoid Models for Virological Studies in Animals: A Cross-Species Perspective

Abstract: Animal models and cell culture in vitro are primarily used in virus and antiviral immune research. Whereas the limitation of these models to recapitulate the viral pathogenesis in humans has been made well aware, it is imperative to introduce more efficient systems to validate emerging viruses in both domestic and wild animals. Organoids ascribe to representative miniatures of organs (i.e., mini-organs), which are derived from three-dimensional culture of stem cells under respective differential conditions mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 137 publications
(503 reference statements)
0
10
0
Order By: Relevance
“…The debate on whether or not engineered cell-based in vitro models, such as organoids, can faithfully reproduce the structures and functions of the original organ in vivo is ongoing ( 37 , 38 ). Although organoid systems are limited in their ability to mimic the properties of complex in vivo tissues relevant to physiological or pathological processes in tissues, organoid cultures are still useful tools for studying fundamental mechanistic questions ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The debate on whether or not engineered cell-based in vitro models, such as organoids, can faithfully reproduce the structures and functions of the original organ in vivo is ongoing ( 37 , 38 ). Although organoid systems are limited in their ability to mimic the properties of complex in vivo tissues relevant to physiological or pathological processes in tissues, organoid cultures are still useful tools for studying fundamental mechanistic questions ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rapid loss of the structure and integrity of stratified organotypic explants is often observed [ 37 ]. Thus, prompt handling after surgeries to transiently retain physiologic relevance of tissue architecture and cellular interactions is required and is prohibitive to long time-course experiments [ 38 ]. Furthermore, these systems are inherently not self-renewing and require patient donors.…”
Section: Meeting In the Middle: 3d Tissue Models To Study Initial Ste...mentioning
confidence: 99%
“…It is now known that many animals including both wildlife and domestic species play an important role in the spread of zoonotic diseases as potential reservoirs. For instance, severe acute respiratory syndrome (SARS), which resulted in a major outbreak worldwide in early 2000s, and the current ongoing pandemic of the new coronavirus 2019 disease (COVID-19) are caused by previously unrecognized coronaviruses which are most likely evolved from bats as a natural reservoir (SARS-CoV and SARS-CoV-2, respectively) ( 18 , 121 ). A recent study demonstrated susceptibility of bat intestinal organoids to SARS-CoV-2 and sustained viral replications in organoids, which could not have been achieved using bat cell lines, by establishing an in vitro infection model ( 122 ).…”
Section: Roles Of Farm and Companion Animal Organoids In One Health I...mentioning
confidence: 99%
“…This study demonstrated previously unculturable novel viruses in established cell lines could be cultured in organoids. Additionally, SARS-CoV-2 has been shown to infect various domestic and wildlife species other than humans including dogs, cats, minks, ferrets, hamsters, lions and tigers ( 121 ). Animal organoids derived from different species would provide an effective tool to evaluate cross-species variations in viral susceptibility or species-specific infectivity of viruses with zoonotic and zooanthroponotic potentials, providing a great alternative to animal models for infection studies.…”
Section: Roles Of Farm and Companion Animal Organoids In One Health I...mentioning
confidence: 99%